Medical Education for Preventive Care: A Role in Reducing Healthcare Costs - Ameneh Marzban (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: In the present era, considering the rising expenses of healthcare and the difficulties associated with chronic diseases and epidemics, it is essential to evaluate the medical education system. Meanwhile, educational approaches based on preventive care can significantly help lower the financial burden on the healthcare system and enhance public health.